Self-tuning control of a chip refiner motor load - Dumont, Guy A. (Automatica (Oxford), 1982)
On a chip refiner the gain of the transfer function between the refiner motor load and the plate gap is subject to a slow drift due to plate wear and to sudden changes in sign due to collapse of the pulp pad. A self-tuning regulator was designed to control motor load by manipulating the plate gap. It uses a recursive least-squares estimator with a variable forgetting factor in conjunction with a Dahlin regulator. Results of plant trials on an industrial thermomechanical pulp production unit show that this regulator is capable of tracking the slow gain drift and of taking proper action in case a pulp pad collapse occurs.